Formação inicial de professores de Educação Física na perspectiva inclusiva: uma análise comparativa sobre Brasil e Portugal - Bonfat, Daniela Lima (2022)
The present dissertation was proposed to investigate the initial teacher education processes of Physical Education teachers from an inclusive perspective in Brazil and Portugal, based on knowledge productions, the analysis of legislation, and the syllabus of Physical Education Center and Sports of the Federal University of Espírito Santo and the Faculty of Human Motricity of the University of Lisbon, as well as we problematize the possible contributions, advances, tensions and/or challenges identified in the investigated realities within the studied theme. For that, we carried out qualiquantitative research, exploratory, and descriptive with approximations of a case study. The instrument used for collecting data was documentary research occurred in the academic productions, the legal documents, syllabus and teaching, research, and extension projects. The analysis of the data was based on the contributions of Bardin (2011) to enhance the interpretation of the research. The results showed that the academic productions from both countries emphasized the teacher education process features and a similar professional role, with intrinsic discussions to the subjects involved, until the general questions about the field, with predominancy on debates with a humanistic character. In outline, Brazil has advances in inclusive legislations in a way to promote a formative process that incentives the debate regarding people with disabilities. Portugal, on the other hand, has invested in a wide concept for inclusive education, which embraces any student that demands support for the educational process. Both realities contribute to think about new strategies to promote a formation in an inclusive perspective.